International Legal Frameworks for Protecting Intellectual Property and Ensuring Academic Freedom - Dihaa, Dihaa Hadaf; Salman, Abdulsatar Shaker; Khalaf, Laith Rafea; Jasim, Bushra Abd Al-Lattif; Vorona, Larisa (Journal of Ecohumanism, 2024)
Background: Intellectual property rights and academic freedom are critical in promoting global innovation and intellectual conversation. However, their cohabitation often raises complicated legal and ethical issues. This article examines how intellectual property rules interact with academic freedom under foreign legal systems. Objective: To examine how international legal tools and treaties combine intellectual property rights protection with academic freedom, stressing the consequences for research and innovation. Methods: This article examines significant international treaties, such as the TRIPS Agreement and the Berne Convention, as well as numerous state legislation, using a comparative legal analysis. It also incorporates qualitative data from interviews with legal professionals and academics, offering a multifaceted picture. Results: The results reflect a complicated ecosystem in which intellectual property regulations can clash with academic freedom values. Notably, strict intellectual property restrictions stymie academic research and cooperation, while too lax ones weaken incentives for innovation. Conclusion: The article finds that international legal frameworks must strike a careful balance to guarantee intellectual property rights and academic freedom. It advocates for policies that promote open access to academic resources while protecting intellectual property rights, implying the need for developing flexible legal instruments for the continually changing world of research and innovation.